Friction torque in grease lubricated thrust ball bearings - Cousseau, Tiago (2011)
Thrust ball bearings lubricated with several different greases were tested on a modified Four-Ball Machine, where the Four-Ball arrangement was replaced by a bearing assembly. The friction torque and operating temperatures in a thrust ball bearing were measured during the tests. At the end of each test a grease sample was analyzed through ferrographic techniques in order to quantify and evaluate bearing wear. A rolling bearing friction torque model was used and the coefficient of friction in full film lubrication was determined for each grease, depending on the operating conditions. The experimental results obtained showed that grease formulation had a very significant influence on friction torque and operating temperature. The friction torque depends on the viscosity of the grease base oil, on its nature (mineral, ester, PAO, etc.), on the coefficient of friction in full film conditions, but also on the interaction between grease thickener and base oil, which affected contact replenishment and contact starvation, and thus influenced the friction torque.